Knowledge Level of Preclinic Students Faculty of Dental Medicine Universitas Airlangga About Halitosis - Putri, Karina Amanda; Rafiantow, Muhammad Rizky; Maulidya, Sheila; Fitria, Diana; Diva, Allya Rania; Hanifan, Raden Mas; Danoediningrat, Hariz Prasetya; Ramadhani, Aulia (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to assess the knowledge of Universitas Airlangga preclinical students’ faculty of dental medicine students on halitosis based on class and gender. Methods: This study was a descriptive research approach by distributing questionnaires about the level of knowledge of Universitas Airlangga Faculty of Dental Medicine preclinical students about halitosis. Results: The study was conducted on 99 respondents, where based on the generation that had the highest level of knowledge was in the class of 2018, while based on gender, men had a slightly higher level of knowledge than women. Conclusion: The results showed as many as 57 respondents (57.6%) had a level of knowledge below the average, while the remaining 42 respondents (42.4%) had a level of knowledge above the average. In the frequency distribution of the knowledge level of halitosis by sex showed that the types of men and women do not have a significant difference, where the majority still have a level of knowledge below the average.